Role of Festivals in Stimulating the Development of Event Tourism - AKHUNDOVA, Aytakin (Theoretical and Practical Research in Economic Fields, 2024)
The research topic related to the role of festivals in event tourism is relevant as the impact of this tourism on the world economy and socio-cultural development is currently growing. Festivals have become key elements of event tourism, attracting huge numbers of tourists, and influencing regional economies, and with increasing globalization and accessibility of travel, festivals are becoming magnets for those seeking new cultural and entertainment experiences. The research aims to analyze and interpret the impact of festivals on the development of event tourism, considering current socio-cultural and economic trends. Among the methods used, analytical, statistical, functional, system analysis, deduction, synthesis, and comparison methods were applied. The study analyzed various aspects of the impact of festivals on event tourism such as economic benefits to regional communities, cultural exchange, media attention (media) and large-scale tourist influx. Different types of festivals (for example, music, culture, sports) and their impact on attracting different types of tourists were examined. The economic benefits that festivals bring to regional communities have been highlighted, which includes an assessment of employment, business growth, impact on trade, investment, and other aspects. The impact of festivals on the socio-cultural dynamics of regions is analyzed, and effective strategies for planning and promoting festivals to maximize their impact on event tourism are investigated. The practical significance lies in the application of the findings to address issues related to festivals to effectively develop event tourism.